2022
DOI: 10.21601/jdet/11584
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Learning as a Solution for Restricted Learning during the COVID-19 Pandemic

Abstract: The proliferation of smartphones and web technology 2.0 raises the possibilities for supporting mobile learning during the COVID-19 outbreak. This quantitative research attempted to justify the use of mobile learning as a potential tool to fill the gap of restricted learning in higher education during this COVID-19 crisis. Respondents were chosen through multi-stage random sampling. A total of 116 teachers and 291 students from a state university in the Philippines answered the online survey. As results indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 17 publications
2
21
0
Order By: Relevance
“…Thom e et al (2019) confirmed a favourable relationship between epistemic value and buying decision making. According to Bacolod (2022), effective online pedagogy played important role in mobile learning during restricted learning caused by pandemic which supports our current study result that perception of value generated from pedagogical aspects is important for MOOC CI.…”
Section: Discussionsupporting
confidence: 86%
“…Thom e et al (2019) confirmed a favourable relationship between epistemic value and buying decision making. According to Bacolod (2022), effective online pedagogy played important role in mobile learning during restricted learning caused by pandemic which supports our current study result that perception of value generated from pedagogical aspects is important for MOOC CI.…”
Section: Discussionsupporting
confidence: 86%
“…Therefore, the preparation for mobile learning would be important to manage future global threats [11]. This finding is in agreement with Bacolod's (2022) findings which showed mobile learning as a crucial learning tool and agreed about its importance during pandemic despite some difficulties in implementation [12]. These findings further support the idea that m-learning is very helpful in improving the study gap during COVID-19 pandemic and education policymakers must incorporate mobile learning technology in educational systems [13].…”
Section: Plos Onesupporting
confidence: 84%
“…Although students have this literacy in computers, seemingly, it does not solve the problem of students if they have learned in the conduct of online learning. In the study of (Bacolod, 2022), it was revealed that both students and teachers still find learning difficulties in their online classes, and this can be traced to their previous learning environment, in which they got direct face-to-face instruction and were aided by the teacher compared to the online learning which is most of the time is self -learning.…”
Section: Discussionmentioning
confidence: 99%